Urban Sprawl From a Comparative Perspective: The Case of US Cities Versus Their Romanian Counterparts. Is There Any Reason Why We Should Worry? (I) - Bogdana NEAMȚU (Transylvanian Review of Administrative Sciences, 2005)
The paper concerns itself with creating a theoretical framework for understanding sprawl within Romanian cities. It has a twofold structure: in the first part the emphasis is on identifying some indicators that best describe this phenomenon. Some key features referred to by American scholars when describing sprawl in the US are reviewed and analyzed. Special consideration is paid to the Romanian context that greatly differs from the American one. Also, this section focuses on possible causes that account for the current pattern of sprawl in Romania. In the second part of the paper some arguments are brought in order to support the idea that sprawl is becoming a serious problem that Romanian urban planners will have to deal with in the near future. Though sprawl may be seen as an indicator for economic growth- this further implies that sprawl has positive aspects, one should not forget the environmental and the aesthetic concerns regarding suburban development. Because cities are expanding at a very rapid pace nowadays, it is necessary for the decision-makers to understand what the pros and the cons for urban sprawl are; also some of its pervasive effects that may not be obvious many years from now need to be more in depth documented.